Upstream Attractiveness of the Brazilian Oil and Natural Gas Sector: An Assessment based on the Stakeholders#x2019; Perceptions (Global Journal of Management and Business Research, 2020)
This study provides an overview of 25 Upstream attributes of the Brazilian oil and natural gas sector and of the country itself, identifying from the industry stakeholders#x2019; perspective the strengths and weaknesses that were aggregated with the support of SPSS (Statistical Package for the Social Sciences) in four factorials: Trade, Regulatory, Prospectivity and Business Environment. The four field surveys which totalled 1,143 structured face-to-face interviews were conducted during the 2012, 2014, 2016 and 2018 editions of Rio Oil
Keywords: oil and natural gas industry in brazil; stakeholder evaluation; attractiveness; regulation; competitiveness